Airway responses to cold air exercise in junior cross-country skiers - Johansson, A. (Mittuniversitetet (Mid Sweden University), 2020)
A common problem among winter sport athletes, especially cross-country skiers, is exercise induced asthma (EIA). Exercise intensity, temperature and humidity are factors that appears to affect EIA. The aim ofthis study was to assess the influence of exercise intensity and climate factors on airway responses to exercise in cold air in junior cross-country skiers. The participants were fourteen high school students whose lung function(FVC, FEV1, FEF25-75and PEF) was measured pre-and post-exercise via spirometer testing. The athletes also completed a questionnaire regarding their post-exercise asthma related symptoms. The results showed a significant effect of type of training onFEF25-75%and PEF. There was a trend towards an effect of type of training on FEV1. Low-intensity training resulted in a greater post-exercise decrease in all measurements.There was a significant effect of temperature/humidity on FEF25-75%and PEF.Warmer and more humid conditions were associated with a greater decrease in both measurements.Regarding temperature and humidity, the results were not the same as the hypothesis nor previous research. The result which indicates that alow exercise intensity results in more severe airway responses, have some support in previous research and can therefore have some bearing. Nonetheless, more research is needed to know whether a low-or a high intensity results in more severe airway responses and an elevated risk for developing EIA.